2018
DOI: 10.1007/s13762-018-1795-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the fuzzy ARTMAP neural network method performance in geological mapping using satellite images and Boolean logic

Abstract: Currently, in executive comparative studies and even in the research studies of natural resources, the use of maps produced by the geological survey forms the basis of geological studies. However, in recent years, remote sensing technology has been introduced as a new and efficient tool for geological studies which in addition to the accuracy has other benefits such as access to the arduous mountainous areas or inaccessible that can help us to prepare geological maps with more accuracy. The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Finally, with the help of simulated models, it was concluded that some types of trees whose developmental trend is expected with significant decline requires a proper forestry management. Arabi Aliabad et al (2018) investigated the land use changes and the way of using lands by remote sensing data of 1973 and 2010. Besides, they simulated the urban growth of Mumbai city for the 10-year period from 2020 to 2030.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, with the help of simulated models, it was concluded that some types of trees whose developmental trend is expected with significant decline requires a proper forestry management. Arabi Aliabad et al (2018) investigated the land use changes and the way of using lands by remote sensing data of 1973 and 2010. Besides, they simulated the urban growth of Mumbai city for the 10-year period from 2020 to 2030.…”
Section: Discussionmentioning
confidence: 99%
“…Remote sensing is of central importance because of certain features such as wide visibility, integration, the use of various electromagnetic energy components to record phenomena, short return periods, the possibility of using hardware and software, low cost and faster inspection (Hamidy et al 2016;Kermani and Rohrbach 2018;Shojaei et al 2018;Nasiri et al 2017;Reinsma 2019). Today, evaluation of ground changes (the conversion of forest, pasture, agricultural lands, and gardens to residential areas and urban facilities) through change detection process using multi-temporal remote sensing imagery is an alternative method for costly, time-consuming and often low-priced methods (Arabi Aliabad et al 2018). Iranmehr (2014) employed TM, ETM + , and OLI Landsat images related to years of 1985, 2003, and 2013 to detect and predict the land use and cover changes around Zayanderud.…”
Section: Introductionmentioning
confidence: 99%
“…There is an extensive body of literature on the use of remote sensing strategies to monitor and manage floods. Research has shown that advancements in science that leverage new techniques for receiving and processing data, as well as the use of software and information processing systems, play a major role in the management of limited water and soil resources [ 16 ]. Similarly, [ 17 ] recommended that the GIS model is one of the most useful methods for evaluating the intensity of soil erosion in the Delichai basin.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In the forward propagation process, the input information is processed layer by layer from the input layer through the hidden layer and then passed to the output layer. If the desired output cannot be obtained in the output layer, it will switch to back propagation, return the error signal along the original connection channel, and modify the weight of the neurons to minimize the error signal [8].…”
Section: Introductionmentioning
confidence: 99%